Shaping light with split lens configurations. (20th September 2016) - Lizana, A; Vargas, A; Turpin, A; Ramirez, C; Estevez, I; Campos, J
Abstract: We present an intuitive and versatile method that can dynamically generate 2D and 3D tailored light patterns. The light structures are generated by dynamically implementing discrete and continuous split lens configurations onto a spatial light modulator. These configurations can be dynamically modified by tuning a reduced number of control parameters with simple physical interpretation. We demonstrate the versatility of the method by experimentally implementing a wide number of structured beams, including optical lattices, a light cone, and vortex beams carrying orbital angular momentum. Compared with other optical illuminators, the advantages of our method are its simple interpretation and control for creating the light structures, and that it is based on a robust, dynamic and easy-to-build optical set-up. The proposed method may be useful in a large number of applications, such as optical trapping, super-resolution imaging or illuminating arrays of photonic switching devices.